Comparison of distortion-product otoacoustic emission and stimulus-frequency otoacoustic emission two-tone suppression in humans - Rasetshwane, Daniel M. (J Acoust Soc Am, 2019)
Distortion-product otoacoustic emission (DPOAE) and stimulus-frequency otoacoustic emission (SFOAE) are two types of acoustic signals emitted by the inner ear in response to tonal stimuli. The levels of both emission types may be reduced by the inclusion of additional (suppressor) tones with the stimulus. Comparison of two-tone suppression properties across emission type addresses a clinically relevant question of whether these two types of emission provide similar information about cochlear status. The purpose of this study was to compare DPOAE suppression to SFOAE suppression from the same ear in a group of participants with normal hearing. Probe frequency was approximately 1000 Hz, and the suppressor frequency varied from −1.5 to 0.5 octaves relative to the probe frequency. DPOAE and SFOAE suppression were compared in terms of (1) suppression growth rate (SGR), (2) superimposed suppression tuning curves (STCs), and (3) STC-derived metrics, such as high-frequency slope, cochlear amplifier gain, and Q(ERB) (ERB, equivalent rectangular bandwidth). Below the probe frequency, the SGR was slightly greater than one for SFOAEs and slightly less than two for DPOAEs. There were no differences in STC metrics across emission types. These observations may provide useful constraints on physiology-based models of otoacoustic emission suppression.